The Effects of Cigarette Smoking on the Cardiovascular System: Mechanisms of Damage, Risk Factors, and Prevention Strategies - Kinga Janowska; Joanna Szydziak; Aleksandra Hrapkowicz; Daria Dąbkowska; Olga Szeidl; Dominika Rehan; Agnieszka Mioskowska (Journal of Education, Health and Sport)
Introduction: Cardiovascular diseases remain the leading cause of morbidity and premature mortality. Even though the prevalence of cigarette smoking has decreased over the last few decades, it is still one of the most important preventable risk factors for cardiovascular diseases. Moreover, recently, an increasing number of people have been transitioning to e-cigarettes, which also influence blood pressure and the cardiovascular system.